Charles Tilly (comp.). The Demographic Transition : True or False?, Historical Studies of Changing Fertility, Princeton, Princeton University Press, 1978. 390 p. - Keyfitz, Nathan (Estudios Demográficos y Urbanos, 1980)
CHARLES TILLY (Соmр.). The Demographic Transition: True or False?, Historical Studies of Changing Fertility, Princeton, Princeton University Press, 1978.